Risk Identification and Prevention of Cross-Industry M & A: A Case Study of Midea's Acquisition of Kolu Electronics - Chen, Yiqiu (International Journal of Global Economics and Management, 2024)
With the rapid development of our country' s economy, the replacement of major industries speed up. In order to seek better development, cross-industry M & A has become an important means to rapidly enter new industries and expand strategic blueprint. Through the case analysis of Midea Group's acquisition of Kolu Electronics, the paper takes pre-acquisition and post-acquisition as the discussion node, and identifies the risks faced by Midea Group as the M & a party, this paper analyzes the industry choice risk, enterprise choice risk, management integration risk and financial integration risk in the early stage of M & A, and puts forward some corresponding risk prevention measures, that is to strengthen the pre-merger investigation, stabilize the core talent to reduce the risk of management integration, seek common ground while reserving differences to reduce the risk of financial integration, for the future cross-industry M & a process of emerging industries risk identification and prevention provides some reference.